2018
DOI: 10.1371/journal.pone.0196199
|View full text |Cite
|
Sign up to set email alerts
|

Stopping at a red light: Recruitment of inhibitory control by environmental cues

Abstract: Environmental cues can influence basic perceptual and attentional processes especially in an emotional context. In the current study, we aimed to investigate the effect of a non-emotional common environmental cue―a traffic light—on a higher cognitive operation―inhibition. In two experiments, we administered a novel version of the stop-signal task, in which the go task was to determine the color of a traffic light. In order to investigate the influence of each of the cues on inhibitory processes, separate track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Importantly, our results suggest that responses are more outcome-insensitive (i.e., habitual) when the stimulus meanings are congruent with our experiences in daily life (e.g., when a traffic light indicating "stop" is red, rather than green, blue or purple). This finding is in line with a previous report of improved inhibitory performance when the stop-signal is red compared to green [22], which provides further support to the notion that an environmentally congruent cue can substantially affect action execution. However, the incongruency-related changes alone are not enough to conclude that a response is habitual; rather this conclusion must be verified by a comparison of the habitual associations (i.e., green-go, red-stop) with the novel control condition Go/NoGo associations (i.e., purple-go, blue-stop).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Importantly, our results suggest that responses are more outcome-insensitive (i.e., habitual) when the stimulus meanings are congruent with our experiences in daily life (e.g., when a traffic light indicating "stop" is red, rather than green, blue or purple). This finding is in line with a previous report of improved inhibitory performance when the stop-signal is red compared to green [22], which provides further support to the notion that an environmentally congruent cue can substantially affect action execution. However, the incongruency-related changes alone are not enough to conclude that a response is habitual; rather this conclusion must be verified by a comparison of the habitual associations (i.e., green-go, red-stop) with the novel control condition Go/NoGo associations (i.e., purple-go, blue-stop).…”
Section: Discussionsupporting
confidence: 92%
“…However, in Experiment 1, green-NoGo accuracy was comparable to that of blue-NoGo or purple-NoGo mappings. A similar pattern has been documented in previous research: Hochman et al found that better stop-signal task performance using red and green light stimuli was primarily driven by a red-stop association as opposed to a green-go association [22]. In light of this report, it could be the case that a green-NoGo impairment is more difficult to detect than the advantage a red-stop association may elicit.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The studies assessing the impact of primary colors-red versus green (or vs. blue) on performance (for a review, see Elliot, 2015)-have also included indicators of motor (e.g., Elliot & Aarts, 2011;Elliot, Maier, Binser, Friedman, & Pekrun, 2009;Meier, D'Agostino, Elliot, Maier, & Wilkowski, 2012;Payen et al, 2011) and cognitive performance, namely attention (Hochman, Henik, & Kalanthroff, 2018), information processing (Soldat, Sinclair, & Mark, 1997), and memory (for a review, see Dzulkifli & Mustafar, 2013). The pattern of findings obtained was not clear-cut: Some studies have found that red (vs. blue or green) inhibits performance, whereas others show that it facilitates it (for a review, see Mehta & Zhu, 2009).…”
Section: The Meanings and Effects Of Red And Green (And Blue)mentioning
confidence: 99%